2020
DOI: 10.3390/ijms21124305
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Analysis of the Full-Length Transcriptomes of Multiple Organs in Pseudotaxus chienii (W.C.Cheng) W.C.Cheng

Abstract: Pseudotaxus chienii, a rare tertiary relict species with economic and ecological value, is a representative of the monotypic genus Pseudotaxus that is endemic to China. P. chienii can adapt well to habitat isolation and ecological heterogeneity under a variety of climate and soil conditions, and is able to survive in harsh environments. However, little is known about the molecular and genetic resources of this long-lived conifer. Herein, we sequenced the transcriptomes of four organs of P. chienii using the Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…This result suggests that when the species adapts to the surrounding environment, gene expression and nucleotide diversity have a reciprocal relationship. This phenomenon might be attributed to gene duplication events occurring in the P. chienii genome during the evolutionary process [43]. Compared with single-copy genes, duplicated genes usually significantly increase the diversity of gene expression, while genetic diversity remains relatively weak [44].…”
Section: Population Gene Expression Variationmentioning
confidence: 99%
“…This result suggests that when the species adapts to the surrounding environment, gene expression and nucleotide diversity have a reciprocal relationship. This phenomenon might be attributed to gene duplication events occurring in the P. chienii genome during the evolutionary process [43]. Compared with single-copy genes, duplicated genes usually significantly increase the diversity of gene expression, while genetic diversity remains relatively weak [44].…”
Section: Population Gene Expression Variationmentioning
confidence: 99%
“…These results indicated that genome size did not correlate with transcriptome size and more genes were covered by multi-organ sequencing than by single organ sequencing. Similarly, the novel strategy of multi-organ FL transcriptome for gene analysis has been used for several nonmodel plants, including Asarum sieboldii (Chen et al, 2020), Pseudotaxus chienii (Liu et al, 2020), and Cephalotaxus oliveri (He et al, 2021).…”
Section: Assessment Of Full-length Transcriptomesmentioning
confidence: 99%
“…The method of Liu et al [57] was used to obtain the total RNA of S. sagittifolia flower buds at different developmental stages. The integrity of the total RNA samples was monitored by the Agilent 2100 system, and the purity of the RNA samples was measured using NanoDrop spectroscopy (Novogene Company, Beijing, China).…”
Section: Rna Extraction and Library Constructionmentioning
confidence: 99%
“…The results predicted by both software packages as 'non-coding' were used as the final long noncoding (lnc)RNA result for the full-length transcriptome. The coding sequences were assembled using the software Cogent [62], and variable shear analysis was then performed by SUPPA [57] as a reference.…”
Section: Other Structural Analysesmentioning
confidence: 99%